Pleistocene distribution of MacConnell’s Bat (Phyllostomidae) suggests intermittent connections between Amazonia and Atlantic Forest - Silva, Felipe Pessoa; da Silva, Lucas Gonçalves; Semedo, Thiago B. F.; Santos, Tamily C. M.; Lopes, Gerson Paulino; Montes, Martin Alejandro; Garbino, Guilherme S. T. (THERYA, 2023)
The historical biogeography of the major South American forested biomes has long intrigued scientists. Paleoclimatic events during the last 130 thousand years promoted connections between forested biomes in the Neotropical region, leading to disjunct distributions of some of the biota. In this context, MacConnell’s Bat, Mesophylla macconnelli, appears to represent a forest-restricted species with its current distribution bisected by dry areas. In this study, we infer past connections between the Amazonia and Atlantic Forest using MacConnell’s Bat and ecological niche models. We obtained 681 records of the species, and estimated its potential distribution during the Last Interglacial (LIG), Last Glacial Maximum (LGM), and current periods. Our generated models, based on 260 filtered occurrence records, had very good predictive power, with AUC and TSS adherence values above 0.9. Temperature seasonality and annual precipitation had the highest relative contribution. The potential distribution for the LIG suggested a suitable area connection between the southwestern Atlantic Forest and southern Cerrado and Amazonia. The potential distribution in the LGM suggests range expansion toward northern and eastern Amazonia. The current and inferred past distributions of Mesophylla macconnelli suggest at least two periods of past connection between Amazon and Atlantic Forest. This pattern is found in other forest-associated vertebrates in South America, suggesting that Pleistocene climatic cycles were central to the generation of disjunct distributions in the region.